KETERAMPILAN MENULIS CERPEN MENGGUNAKAN METODE KELILING KELOMPOK SISWA KELAS IX SMP NEGERI 3 KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Hendrisman Hendrisman; Rita Arianti (Jurnal Akrab Juara, 2018)
This study aims to describe the Skill of Writing Short Stories Using The Student Group Method Class IX SMP Negeri 3 District Harau District Lima Puluh city. This type of research is quantitative research using descriptive method. The research population of students of class IX, amounting to 154 students. Sampling through cluster random sampling technique and selected class IX.1 which amounted to 22 students. Based on the results of data analysis shows that the Skill of Writing Short story Using Class Sharing Method Class IX SMP Negeri 3 District Harau District Lima Puluh City in general with average value 84 with good qualification. The writing skills of the short stories in terms of the three indicators are: (1) the intrinsic element of the short story is 92 with excellent qualification, (2) the capitalization is 72.72 with the qualification is almost enough, and (3) the use of punctuation is 87,5 with excellent qualifications, So, it can be concluded that the application of a good grouping method for students' short story writing skills.